ANALYSIS OF FUNCTIONAL CAPACITY IN ELDERLY WHO HAD FALLS AND WHO DIDN'T: A CASE-CONTROL STUDY (Movimenta (ISSN 1984-4298), 2022)
ABSTRACTIntroduction: Life expectancy has increased due to the predominance of chronic diseases replacing infectious diseases, increasing morbidity. Objective: To analyze the functional capacity of elderly people who had falls, and those who did not have falls in the last year. Methods: A case-control study composed of two groups, group 1 consisted of elderly people who had fallen in the last year and group 2 consisted of elderly people who had not. The International Falls Efficacy Scale (FES-I-Brasil), the International Physical Activity Level Questionnaire (IPAQ), the Anterior Functional Reach Test (TAF), the Timed Get Up and Go (TUG) and the palm grip test. Results: 27 elderly people were included in the study, 7 from the faller group and 20 from the non-faller group. In the group of fallers, the time of the TUG was longer, as well as the FES-I-Brasil, however the TAF and the values ​​of both right and left hand grip were lower when compared to the group of non-fallers. On the IPAQ scale, values ​​were higher in all stratifications in the group of non-fallers, except for “irregularly active A”. No variable was associated with falls in the elderly. Conclusion: Most of the elderly who performed exercises frequently had a good functional capacity, their previous balance was unchanged, as well as a moderate and sporadic risk of falls and a lower risk of future functional dependence, considering the level of active or irregular activity. active.Keywords: Aging. Physical activity. Sedentary behavior.
Keywords: Aging. Physical activity. Sedentary behavior.